2016
DOI: 10.1007/s00359-016-1124-x
|View full text |Cite
|
Sign up to set email alerts
|

How females of chirping and trilling field crickets integrate the ‘what’ and ‘where’ of male acoustic signals during decision making

Abstract: In crickets acoustic communication serves mate selection. Female crickets have to perceive and integrate male cues relevant for mate choice while confronted with several different signals in an acoustically diverse background. Overall female decisions are based on the attractiveness of the temporal pattern (informative about the 'what') and on signal intensity (informative about the 'where') of male calling songs. Here, we investigated how the relevant cues for mate choice are integrated during the decision pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For example, one study used crickets to identify how protein and carbohydrate levels influenced weight, muscle mass, and fat reserves [86]. Crickets have been widely used within behavioral tests [87][88][89]. For example, one study used crickets with a plus-shaped maze to examine predator-induced stress and found that the crickets showed consistent behavioral responses in their tests [90].…”
Section: Animalsmentioning
confidence: 99%
“…For example, one study used crickets to identify how protein and carbohydrate levels influenced weight, muscle mass, and fat reserves [86]. Crickets have been widely used within behavioral tests [87][88][89]. For example, one study used crickets with a plus-shaped maze to examine predator-induced stress and found that the crickets showed consistent behavioral responses in their tests [90].…”
Section: Animalsmentioning
confidence: 99%
“…Males produce a conspicuous longdistance calling song to attract females from afar and, once in close proximity, switch to a lower intensity courtship song that is required before females will mount to receive the sperm-containing packet. Female crickets show the strongest preferences for temporal features of the calling and courtship songs (Gabel et al, 2016), and both songs contribute to precopulatory isolation between species (Fitzpatrick and Gray, 2001;Jang and Gerhardt, 2006;Maroja et al, 2014;Gray et al, 2016;Hennig et al, 2016). Closely related Hawaiian swordtail crickets (Laupala sp.…”
Section: Coupling and Mismatch Of Signals And Chooser Preferencesmentioning
confidence: 99%
“…Within Gryllus, the two species are not close relatives (electronic supplementary material, figure S2), but both typically call with a three to five pulse chirp at unusually slow pulse rates: at 248C, G. firmus average about 18 p s 21 [27], whereas G#13 average about 10 p s 21 (DA Gray 2005, unpublished data); these are among the slowest pulse rates in North American Gryllus. Because pulse rate is consistently a principal song feature important in cricket song recognition [16,28], examination of species with low pulse rates might reveal unexpected effects of signal processing.…”
Section: Introductionmentioning
confidence: 99%